EVALUATION BUSINESS POND FISHING ESPECIALLY RICKY FISHING POND IN THE TANGKERANG LABUAI VILLAGE DISTRICTS BUKIT RAYA PEKANBARU CITY - Renni Silaban; M. Ramli; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted on 25th May until 7th June 2012. This study aims todescribe the general business management, total investment, profits, profitability, and returnsthe length of venture capital invested in the Ricky fishing pond. The method used in this studyis a case study method with four respondents.The results of this study indicate that the total investment by the business owner Rickyfihing pond of Rp 713.039.000. Gains derived of Rp 100.271,500. BCR of 1,21. Returns thelength of venture capital invested in the fishing pond is for 7 years and 1 months.Keyword : Evaluation Business, Fishing Pond, Ricky Fishing Pond